Combining Data Longevity with High Storage Capacity—Layer‐by‐Layer DNA Encapsulated in Magnetic Nanoparticles - Chen, Weida D.; Kohll, A. Xavier; Nguyen, Bichlien; Koch, Julian; Heckel, Reinhard; Stark, Wendelin J.; Ceze, Luis; Strauss, Karin; Grass, Robert N. (Advanced Functional Materials, 2019)
In this paper the practical density of long‐term DNA storage is increased. Specifically, the DNA weight loading of silica sphere DNA storage is increased to 3.4 wt%, a ten‐fold increase compared to the previous state‐of‐the‐art. By applying a Layer‐by‐Layer (LbL) design with alternating layers of DNA and a polycationic molecule, namely polyethyleneimine (PEI), another dimension to DNA surface binding onto magnetic nanoparticles is added. A protective silica layer is grown on top of the multilayered nanoparticles to shield the DNA from external sources of damage. Accelerated aging experiments of the nanoparticles and the subsequent quantification of DNA stability via qPCR show a significantly lower degradation rate compared to unprotected DNA. The novel material is compared to previous DNA storage technologies, outperforming those in DNA storage density as well as stability. Finally, the storage of an 83 kB digital file in DNA through a successful readout of a 4991 oligonucleotide pool is demonstrated from particle encapsulation, through accelerated aging, to sequencing.